FAMILIAL CHRONIC MYELOCYTIC LEUKEMIA: THE OCCURRENCE IN FIRST COUSINS IN JOS, NORTH CENTRAL NIGERIA - Dr. Damulak Obadiah Dapus; Dr. Jatau Ezra Danjumma; Dr. Zakari Ayuba; Dr. Egesie J Ochaka (Medico Research Chronicles, 2019)
Introduction: Chronic myeloid leukemia is a leukemic myeloproliferative disorder that is rarely diagnosed in members of the same family. Aim: We report the occurrence of chronic myeloid leukemia in male first cousins in Jos. Cases report: Two cousins 37 years and 31 years old were referred to our department for leucocytosis in the first patient and priapism and leucocytosis in the second. Full blood count and bone marrow aspiration cytology in both cases revealed granulocytic leucocytosis with all the stages of myeloid maturation in peripheral blood and marrow myeloid hyperplasia in keeping with chronic myeloid leukemia. Treatment with tyrosine kinase inhibitor (TKI) was delayed in both, due to financial constraints for transportation to the treatment center in Nigeria. Cytoreduction with hydroxyurea was the initial treatment instituted. Even with the eventual commencement of imatinib mesylate, the outcome was still poor in the second patient who transformed and died within one year. Conclusion: Chronic myeloid leukemia has occurred in family members in our environment.